A new area of stem cell therapy for Parkinson disease - Hassan, Khaled M.; Alqarni, Zahra H.; Almontashri, Ali A.; Allubly, Ahmed M.; Alalmaee, Khalid A.; Alhalawani, Fatemah A.; Alshalfan, Fahad M.; Anbarserri, Muayad M.; Almalki, Mohammed S.; Tai, Mohammed A.; Felemban, Weaam A.; Alhassani, Mansoor D.; et al. (International Journal Of Community Medicine And Public Health, 2020)
No treatment currently can be used in order to slow or even stop the progression of Parkinson’s disease. Nowadays, researchers are already using stem cells to grow dopamine-producing nerve cells in the lab so that they can study the disease, especially in those cases where there is a known genetic cause for the condition. The development of the advanced cellular therapies and using induced pluripotent stem cells is making it possible to combat the progression of the disease without the resulting motor complications. It has been shown that the transplantation of many cell sources leads to reduce Parkinson’s disease symptoms in animal models.